STRATEGI BERTAHAN HIDUP DAN PERILAKU EKONOMI RUMAHTANGGA PEMBUDIDAYA IKAN SISTEM KJA DI DESA ETI KABUPATEN SERAM BAGIAN BARAT - Stevanus Marelly Siahainenia; Johanis Hiariey; Gianie Vergie Kayadoe (Universitas Pattimura, 2023)
The farmer's economic dilemma is waiting for the fish harvest which is around 6-8 months, this condition makes it difficult for farmers to fulfill their daily basic needs. The aim of this research is to find out the survival strategy and to analyze economic behavior related to the decision on the sustainability of the cultivator's household economy. This research was conducted from February to May 2022, using a survey method approach. The use of respondents was 11 cultivator households in Eti Village. The data analysis technique was carried out descriptively qualitatively to find out survival strategies, while quantitatively to analyze economic behavior (variable relations with production and consumption based on a correlation analysis approach. The results showed that the survival strategy of fish cultivating households in Eti Village included an active strategy, namely diversification work by husband and wife, passive strategy by managing frugal lifestyle by wife and networking strategy by utilizing social network by husband and wife Family economic sustainability is reflected in personal household activities as producers and consumers Behavior of fish cultivator households as producers or cultivators in where the decision to produce is closely related to production costs and the amount of labor, while the decision to consume is related to the number of family dependents.